Feeder layer-free in vitro assay for screening antitrypanosomal compounds against Trypanosoma brucei brucei and T. b. evansi - Kaminsky, R.; Zweygarth, E. (American Society for Microbiology, 1989)
A drug-susceptible Trypanosoma brucei brucei stock, a multidrug-resistant T. b. brucei stock, and a T. b. evansi stock resistant to two commercial trypanocides were adapted to a feeder layer-free culture system. Bloodstream forms were grown continuously in a liquid medium at 37 degrees C in 4% CO2 in air. Samples of trypanosome populations in the logarithmic growth phase were incubated with various concentrations of commercial and experimental compounds. Growth inhibition was monitored after a 24-h incubation and quantified by comparing the number of generations between control and drug-treated cultures. Some of the experimental compounds [taxol, formicin B, thioridazine, Ro 15-0216, and DL-alpha-(difluoromethyl)ornithine hydrochloride monohydrate] showed activity against both drug-susceptible and drug-resistant trypanosomes. Other compounds [sinefungin, 1,3,5-triacetylbenzene tris(guanylhydrazone)trimethanesulfonate hydrate, and 9-deazainosine] which inhibited the growth of drug-susceptible trypanosomes showed little or no effect upon drug-resistant parasites. Gossypol, however, had no antitrypanosomal effect on either trypanosome stock. The results obtained in this study correlate with observations obtained from drug screening in mice. The main advantages of the described in vitro screening assay are as follows: (i) lower amounts of drugs are required, (ii) results are obtained more rapidly, (iii) animals are not necessary, and (iv) the method is less labor intensive. These advantages result in an economical and rapid assay for primary drug screening.